Development of a core capability framework for qualified health professionals to optimise care for people with osteoarthritis: an OARSI initiative. Issue 2 (February 2020) - Hinman, R.S.; Allen, K.D.; Bennell, K.L.; Berenbaum, F.; Betteridge, N.; Briggs, A.M.; Campbell, P.K.; Dahlberg, L.E.; Dziedzic, K.S.; Eyles, J.P.; Hunter, D.J.; Skou, S.T.; et al.
Summary: Objective: Develop a generic trans-disciplinary, skills-based capability framework for health professionals providing care for people with OA. Design: e-Delphi survey. An international inter-professional Delphi Panel (researchers; clinicians; consumer representatives) considered a draft framework (adapted from elsewhere) of 131 specific capabilities mapped to 14 broader capability areas across four domains (A: person-centred approaches; B: assessment, investigation and diagnosis; C: management, interventions and prevention; D: service and professional development). Over three rounds, the Panel rated their agreement (Likert or numerical rating scales) on whether each specific capability in Domains B and C was essential (core) for all health professionals when providing care for all people with OA. Those achieving consensus (≥80% of Panel) rating of ≥ seven out of ten (Round 3) were retained. Generic domains (A and D) were included in the final framework and amended based on Panel comments. Results: 173 people from 31 countries, spanning 18 disciplines and including 26 consumer representatives, participated. The final framework comprised 70 specific capabilities across 13 broad areas i) communication; ii) person-centred care; iii) history-taking; iv) physical assessment; v) investigations and diagnosis; vi) interventions and care planning; vii) prevention and lifestyle interventions; viii) self-management and behaviour change; ix) rehabilitative interventions; x) pharmacotherapy; xi) surgical interventions; xii) referrals and collaborative working; and xiii) evidence-based practice and service development). Conclusion: Experts agree that health professionals require an array of skills in person-centred approaches; assessment, investigation and diagnosis; management, interventions and prevention; and service and professional development to provide optimal care for people with OA.